2009
DOI: 10.1111/j.1600-0625.2009.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol regulates melanogenesis in human epidermal melanocytes and melanoma cells

Abstract: Cholesterol is important for membrane stability and is the key substrate for the synthesis of steroid hormones and vitamin D. Furthermore, it is a major component of the lipid barrier in the stratum corneum of the human epidermis. Considering that steroid hormone synthesis is taking place in epidermal melanocytes, we tested whether downstream oestrogen receptor/cAMP signalling via MITF/tyrosine hydroxylase/tyrosinase/pigmentation could be possibly modulated by cholesterol. For this purpose, we utilized human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 58 publications
1
47
2
Order By: Relevance
“…Cell pellets were dissolved in 1.0 N NaOH containing 10% DMSO and heated at 80°C for 1 h and suspensions were clarified by centrifugation for 10 min at 10 000 g. The amount of melanin was determined spectrophotometrically based on the absorbance at 475 nm (21)(22)(23).…”
Section: Melanin Quantification Assaymentioning
confidence: 99%
“…Cell pellets were dissolved in 1.0 N NaOH containing 10% DMSO and heated at 80°C for 1 h and suspensions were clarified by centrifugation for 10 min at 10 000 g. The amount of melanin was determined spectrophotometrically based on the absorbance at 475 nm (21)(22)(23).…”
Section: Melanin Quantification Assaymentioning
confidence: 99%
“…Various melanoma cell lines have been previously used as models to study the regulation of melanogenesis and the mechanisms of action of promising antimelanogenic agents (Nawarak et al, 2008;Chung et al, 2009;Schallreuter et al, 2009). Moreover, poorlypigmented cells have been previously shown to be more susceptible to UVA-induced oxidative stress (Kvam and Dahle, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Of these hormones, steroids and vitamin D play important roles in cellular and biochemical signalling pathways. Interestingly, a recent study has reported that cholesterol has pro-melanogenic effects in both human epidermal melanocytes and FM55 melanoma cells (1). Cholesterol was reported to initially stimulate cyclic adenosine monophosphate (cAMP) release and activate the transcription of related genes via oestrogen receptor b, with consequent stimulation of cAMP response element-binding protein (CREB)/microphthalmia-associated transcription factor (MITF)/tyrosinase pathways.…”
Section: Introductionmentioning
confidence: 99%
“…This is currently a major issue in the treatment of melanoma by immunotherapy with monoclonal antibodies (anti-CTLA4/PD1 antibody), vaccines and tumor-infiltrating lymphocytes (TILs) (1).…”
Section: Introductionmentioning
confidence: 99%